2022
DOI: 10.1109/access.2022.3173348
|View full text |Cite
|
Sign up to set email alerts
|

An Adaptive Hybrid Control Architecture for an Active Transfemoral Prosthesis

Abstract: The daily usage of a prosthesis for people with an amputation consists of phases of intermittent and continuous walking patterns. Based on this observation, this paper introduces a novel hybrid architecture to control a transfemoral prosthesis, where separate algorithms are used depending on these two different types of movement. For intermittent walking, an interpolation-based algorithm generates control signals for the ankle and knee joints, whereas, for continuous walking, the control signals are generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…process by which the required motor speed during a gait segment was calculated by dividing the standard gait-segment speed by the ratio of standard gait cycle time [36] to the time taken by the subject during the previous gait cycle, ensured the possibility of an infinitely varying gait speed. In the current implementation, the determination of whether the subject is at rest or walking is achieved by counting the number of steps taken with the prosthesis [37]. As long as the step count remains 0, the prosthesis is considered to be at rest, and the controller maintains a neutral angle.…”
Section: A Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…process by which the required motor speed during a gait segment was calculated by dividing the standard gait-segment speed by the ratio of standard gait cycle time [36] to the time taken by the subject during the previous gait cycle, ensured the possibility of an infinitely varying gait speed. In the current implementation, the determination of whether the subject is at rest or walking is achieved by counting the number of steps taken with the prosthesis [37]. As long as the step count remains 0, the prosthesis is considered to be at rest, and the controller maintains a neutral angle.…”
Section: A Discussionmentioning
confidence: 99%
“…However, due to the nature of the data in the Y axis throughout the gait cycle, it is difficult to directly utilize the Y accelerometer data alone to uniquely identify the stance and swing phases of the gait. To use the Y accelerometer data for this characterization, it is possible to couple it with an oscillator of variable phase and frequency, as shown in our previous work [37]. However, since changes to the oscillator parameters require at least a couple of gait cycles, an alternative control method is investigated in this study.…”
Section: A Observationsmentioning
confidence: 99%
“…Investigation of kinematic and kinetic parameters showed that weight-activated braking knee had prolonged swing-phase duration, a higher range of motion, earlier ankle push-off, and greater anterior pelvic tilt. Moreover, two distinct algorithms for intermittent and continuous walking created command signals for the knee and ankle joints, as well as a transition strategy from one method to the other [50]. They followed knee accelerations, number of steps taken, knee and ankle joint references, gait phase, and detected mode of the prosthesis to produce requisite command signals for smooth switching as per requirement.…”
Section: Gait Patternsmentioning
confidence: 99%